Heroes of the campus: the records of a few of those knightly souls who, burning out for God, kindled unquenched fires in the lives of their fellow students - Cochran, Joseph W. (Westminster Press, 1917)
A word at the beginning.--Horace Tracy Pitkin, of Yale.--Pitt Gordon Knowlton, of Oberlin.--Kin Takahashi, of Maryville.--Arthur Frame Jackson, of Cambridge.--Hugh McAllister Beaver, of Pennsylvania State College.--Isabella Marion Vosburgh, of Mount Holyoke.--Forbes Robinson, of Cambridge.--William Whiting Borden, of Yale.--Ion Keith Falconer, of Cambridge.--Samuel John Mills, of Williams.--Elijah Kellogg, of Bowdoin.--David Yonan, of Davidson.--Horace William Rose, of Beloit.--Bibliography (p. 168)